2018
DOI: 10.17010/ijom/2018/v48/i1/120734
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Empirical Relationship Between Service Quality, Trust, Satisfaction, and Intention of Customers Purchasing Life Insurance Products

Abstract: The purpose of this paper was to identify the key SERVQUAL factors for consumer purchase intention in the context of life insurance products in Malaysia. The study was performed based on primary data using a self-administered questionnaire from the Klang valley region of Malaysia. Using a cross-sectional study, a total of 215 usable responses were collected using convenience sampling technique. To measure customer satisfaction, trust, and purchase intention, seven key SERVQUAL factors were utilized, that is, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 0 publications
2
39
0
2
Order By: Relevance
“…Risk aversion instrument in section E was adapted from financial risk tolerance questionnaire of Jacobs-Lawson & Hershey (2005). Section F of the questionnaire measured respondent's evaluation on the sales agent which effected their insurance purchasing behavior were also based on previous literatures (Bieck et al, 2012;Chimedtseren & Safari, 2016;Hasyim, 2017;Panigrahi et al, 2018;Yu & Tseng, 2016). Five items were identified to measure the persuasion construct in section G based on the literature review which is trustworthy, emotion, clarity, persistent and overall persuasion (Bieck et al, 2012;Boubehrezh & Iraji, 2013;Gadzhiyeva & Sager, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Risk aversion instrument in section E was adapted from financial risk tolerance questionnaire of Jacobs-Lawson & Hershey (2005). Section F of the questionnaire measured respondent's evaluation on the sales agent which effected their insurance purchasing behavior were also based on previous literatures (Bieck et al, 2012;Chimedtseren & Safari, 2016;Hasyim, 2017;Panigrahi et al, 2018;Yu & Tseng, 2016). Five items were identified to measure the persuasion construct in section G based on the literature review which is trustworthy, emotion, clarity, persistent and overall persuasion (Bieck et al, 2012;Boubehrezh & Iraji, 2013;Gadzhiyeva & Sager, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Hwang (2014) and Zhao et al (2018) opined that aptitude, kindness and reliability are vital predecessor issues that influence a person's payment decision and use of the online platform. Panigrahi et al (2018) found that trust has a positive impact on the intention to purchase life insurance products. Therefore, quality of service and trust are essential instruments to attract the customer and influence the purchase of products in insurance companies.…”
Section: Trust and Purchase Intentionmentioning
confidence: 99%
“…Trust has a powerful impact on price fairness, and when the digitalized corporations are satisfied with the features of the online portal and realize that features are near to their expectations, then they pay for this service (Mandira et al, 2018). Panigrahi et al (2018) concluded that trust significantly impacts digitalized corporation's purchase and paying determination. Some studies depicted a positive affiliation between pricing and trust (Guspul, 2014).…”
Section: Relating Price Fairness To Trustmentioning
confidence: 99%